Silicon-based negative electrode material with high specific volume and high power and preparation method thereof
By depositing silicon particle units on the carbon skeleton and using gas-phase carbon and solid phase coating, the problem of expansion of silicon-based negative electrode materials during charging and discharging is solved, and the improvement of high specific capacity and high power performance is achieved.
Patent Information
- Application Number
- CN202411917478.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
The existing silicon-based anode materials are prone to expand during charging and discharging, resulting in short cycle life and insufficient conductivity of porous carbon, making it difficult to meet high power requirements.
By depositing silicon particle units on the carbon framework and using a gas-phase carbon and solid phase coating, a multi-layer structure is formed to limit the expansion of the silicon material, improve cycling performance, and improve the conductivity of the material.
The high specific capacity and high power performance of silicon-based negative electrode materials are achieved, which extends the cycle life, avoids side reactions and gas production, and reduces costs.
Smart Images

Figure BDA0005207152810000091 
Figure HDA0005207152820000011 
Figure HDA0005207152820000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a silicon-based negative electrode material with high specific capacity and high power and a preparation method thereof. Background Art
[0002] With the vigorous development of the new energy industry, the requirements for the performance of lithium-ion batteries are increasing. As one of the four main materials of lithium-ion batteries, negative electrode materials play a role in energy storage and release in lithium batteries. Traditional graphite negative electrode materials have approached their theoretical specific capacity limit and are difficult to meet the needs of further improving battery energy density. Therefore, finding negative electrode materials with higher specific capacity has become the focus of industry research. Silicon-based negative electrode materials have become the most promising new generation of lithium battery negative electrode materials due to their high theoretical specific capacity (up to 4200mAh / g, more than ten times that of graphite), good safety, abundant reserves and low cost. However, the intrinsic properties of silicon determine its poor conductivity, which easily causes high volume expansion rate of local silicon materials during large current charging and discharging, and relatively short cycle life. Therefore, silicon-based negative electrode materials with high specific capacity and excellent rate performance came into being.
[0003] At present, nano-silicon produced by gas phase deposition of silane gas cracking on porous carbon with small pore size is generally used to reduce the expansion of silicon during charging and discharging, so as to improve the cycle life. For example, CN118970021A discloses a silicon-based negative electrode composite material and its preparation method and application, wherein the silicon-based negative electrode composite material includes porous carbon and porous silicon-carbon material composed of nano-amorphous silicon deposited in the pores inside the porous carbon, an amorphous carbon layer, and a composite coating layer composed of metal oxide and solid electrolyte. Nano-silicon deposited by gas phase silicon is difficult to deposit uniformly due to the limitation of porous carbon pores, which easily causes excessive local deposition and causes expansion and breakage during charging and discharging, limiting the specific capacity of silicon-based negative electrode materials, and porous carbon itself has poor conductivity and is difficult to meet the high power requirements of materials. Although the patent adds metal oxides, solid electrolytes, etc. as coating layers to improve its power performance, when the silicon material expands, the 0-dimensional metal oxides, solid electrolytes, etc. are easy to lose electrical contact and fail to achieve the expected effect.
[0004] The invention of patent CN118693267A discloses a low-expansion, high-power lithium-silver co-doped nano-silicon-carbon composite material. The composite material presents a core-shell structure, with the core being lithium-doped porous nano-silicon, and the shells are metallic silver first shell and amorphous carbon second shell from the inside to the outside. The composite material uses the low expansion of porous nano-silicon obtained by disproportionation reaction and pickling, and doping metallic lithium in its core to improve the initial efficiency of the material and depositing silver in the pores of the core to improve the electronic conductivity of the material, thereby improving power performance and fast charging performance. However, lithium-silver doping involves silver mirror reaction, pickling, etc. The silver mirror reaction has strict requirements on conditions, low product yield, many defects, and great uncertainty in improving the power performance of the material. In addition, there is an explosion risk in the process operation process, and pickling will also bring many environmental problems, high cost, and difficulty in industrial mass production. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a silicon-based negative electrode material with high specific capacity and high power and a preparation method thereof. The problem of stress concentration of silicon material aggregation is solved by the carbon skeleton, the problem of coating uniformity is solved by gas phase carbon attachment, and the problem of coating shell strength is solved by solid phase coating. It can not only limit the expansion of silicon material and improve the cycle performance, but also isolate the silicon material from contact with the electrolyte, avoiding the occurrence of side reactions and gas production.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: Provide a silicon-based negative electrode material with both high specific capacity and high power, which includes, from the outside to the inside, a second carbon layer, a first carbon layer, a large aspect ratio conductive agent winding layer and an inner core, wherein the inner core is a carbon skeleton adsorbed with silicon particle units, and the particle size of the silicon particle unit is D 95 ≤20nm, the pore size of the carbon skeleton is 10-25nm, the aspect ratio of the large aspect ratio conductive agent is 20-5000, the thickness of the first carbon layer is 1-10nm, and the thickness of the second carbon layer is 5-500nm.
[0007] The present invention also provides a method for preparing the above-mentioned silicon-based negative electrode material with both high specific capacity and high power, which comprises the following steps in sequence:
[0008] (1) In a nitrogen atmosphere, add the dried silicon powder to the alcohol reagent and mix evenly, then grind to silicon particles D 50 ≤30-100nm, then add a grinding aid, continue grinding for 1-5h, then add a carbon skeleton, continue grinding until the solid content of the silicon slurry at the outlet is reduced to 20-50% of the original solid content, filter, and obtain a carbon skeleton adsorbed with silicon particle units;
[0009] (2) using an alcohol reagent to clean the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution dispersed with a conductive agent with a large aspect ratio, stirring evenly and drying to obtain an intermediate product;
[0010] (3) The intermediate product is placed in an inert atmosphere for a primary calcination, and then transferred to a fluidized bed for gas phase cracking to deposit carbon, thereby obtaining a primary coating product;
[0011] (4) The primary coated product is mixed with heavy oil and then subjected to solid phase surface melt coating to obtain a secondary coated product, which is then placed in an inert atmosphere for secondary calcination, sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
[0012] Furthermore, in step (1), water and oxygen are removed under a nitrogen atmosphere, the dew point is ≤-30°C, and the oxygen content is ≤0.5%.
[0013] Furthermore, in step (1), the solid content of silicon powder after adding ethanol is 8-16%.
[0014] Furthermore, in step (1), the diameter of the zirconium beads used in grinding is 0.02-0.2 mm.
[0015] Furthermore, in step (1), the grinding aid is at least one of acrylic acid, stearic acid, tannic acid and acrylamide, and the amount of the grinding aid added is 1-20% of the mass of the silicon powder.
[0016] Further, in step (1), the carbon skeleton is at least one of porous carbon, activated carbon and foamed carbon, and the carbon skeleton particle size D 50 The particle size is 4-12 μm, and the added amount is 0.5-20% of the mass of silicon powder.
[0017] Furthermore, in step (1), filtering is performed using a 400-5000 mesh sieve.
[0018] Furthermore, in step (2), during drying, spray drying, stirring drying, static drying or freeze drying is adopted.
[0019] Furthermore, in step (2), the high aspect ratio conductive agent is at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes and vapor-grown carbon fibers.
[0020] Furthermore, in step (1) and step (2), the alcohol reagent is at least one of ethanol, ethylene glycol, hexylene glycol, isopropanol, allyl alcohol and NMP.
[0021] Furthermore, in step (3), the calcination is carried out at a temperature of 400-800° C. for 3-20 hours.
[0022] Furthermore, in step (3), vapor phase pyrolysis deposition is performed at a temperature of 650-1700° C. for 5-20 hours.
[0023] Furthermore, in step (3), when the carbon is deposited by gas phase cracking, the carbon source is at least one of methane, acetylene, ethylene and propylene.
[0024] Furthermore, in step (4), the solid phase surface is melt-coated at a temperature of 250-500° C. for 5-12 hours.
[0025] Furthermore, in step (4), the heavy oil is at least one of solid asphalt and liquid asphalt; and the amount of heavy oil added is 2-40% of the mass of the silicon powder.
[0026] Furthermore, in step (4), secondary calcination is carried out at a temperature of 600-1200° C. for 3-20 hours.
[0027] The present invention has the following beneficial effects:
[0028] 1. The proportion of active silicon in the silicon-based negative electrode material of the present invention is high, so the specific capacity is high. The added large aspect ratio conductive agent can significantly improve the power performance of the material, especially during high-power charging and discharging, it can match the expansion of the material to keep it in electrical contact. The carbon skeleton solves the problem of stress concentration in silicon materials, the gas phase carbon attachment solves the problem of coating uniformity, and the solid phase coating solves the problem of coating shell strength. It can not only limit the expansion of silicon materials and improve cycle performance, but also isolate the silicon materials from contact with the electrolyte, avoiding side reactions and gas production.
[0029] 2. Silicon-based negative electrode material of the present invention, particle size D 95 The ultra-fine 20-level silicon particle unit of ≤20nm is made by sand milling, with high safety in mass production, large production capacity and good consistency. Moreover, the silicon particle unit below 20nm will not break during charging and discharging, and has high cycle stability. The carrier of the silicon particle unit is a carbon skeleton with a pore size of 10-25nm, which can prevent the silicon particles that do not meet the size standards from being adsorbed, and secondly provide carbon skeleton support, absorption and expansion, and improve the rate performance of silicon-based materials. The large aspect ratio conductive agent wound in the middle can not only improve the rate performance, maintain contact when the silicon material expands, but also has a certain effect of limiting the volume expansion of the silicon material. The first layer of carbon coating adopts the vapor deposition method, which can be uniform and dense, and can make up for the defects of the second layer of solid phase coating, isolating the silicon material from contacting the electrolyte, but the coating layer is thin and the cost is high. The second layer of carbon coating adopts solid phase melting coating, and the coating layer is thick, which can not only limit the volume expansion of the internal silicon material, but more importantly, it can isolate the silicon material from direct contact with the electrolyte and cause side reactions, but it is easy to have defects, and the advantage is low cost and easy to mass produce. The present invention adopts two coating processes, which can take advantage of each, reduce the amount of amorphous carbon generated by coating, improve the specific capacity of silicon-based materials, and achieve low-cost, high-performance coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of a silicon-based negative electrode material having both high specific capacity and high power according to the present invention;
[0031] Figure 2This is a SEM image of the silicon-based negative electrode material with high specific capacity and high power obtained in Example 1;
[0032] Figure 3 The first charge and discharge curves of the products obtained in Examples 1-4 and Comparative Examples 1-3;
[0033] Among them, 1. the second carbon layer; 2. the first carbon layer; 3. the large aspect ratio conductive agent winding layer; 4. the carbon skeleton; 5. the silicon particle unit. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0035] like Figure 1 As shown, the present invention provides a silicon-based negative electrode material with both high specific capacity and high power, which includes, from the outside to the inside, a second carbon layer 1, a first carbon layer 2, a large aspect ratio conductive agent winding layer 3 and an inner core, wherein the inner core is a carbon skeleton 4 adsorbed with silicon particle units 5, and the particle size of the silicon particle unit 5 is D 95 ≤20nm, the pore diameter of the carbon skeleton 4 is 10-25nm, the aspect ratio of the high aspect ratio conductive agent is 20-5000, the thickness of the first carbon layer 2 is 1-10nm, and the thickness of the second carbon layer 1 is 5-500nm.
[0036] Example 1
[0037] A method for preparing a silicon-based negative electrode material with both high specific capacity and high power comprises the following steps in sequence:
[0038] (1) Nitrogen is introduced into the tank containing ethanol to remove water and oxygen in the tank. The dew point is ≤-30°C and the oxygen content is ≤0.5%. The dried silicon powder is added to the ethanol at a solid content of 10% and mixed evenly. The silicon powder is ground into silicon particles D by a sand mill. 50 ≤60nm, then add tannic acid, a grinding aid, accounting for 8% of the mass of the silicon powder, continue grinding for 3 hours, switch the tank discharge mode, and then add a carbon skeleton (activated carbon) accounting for 5% of the mass of the silicon powder, and continue grinding until the solid content of the silicon slurry at the discharge port is reduced to 25% of the original solid content, and filter with an 800-mesh screen to obtain a carbon skeleton adsorbed with silicon particle units;
[0039] (2) using ethanol to wash away the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution in which a high aspect ratio conductive agent (single-walled carbon nanotubes, with an aspect ratio of 3000) accounting for 0.1% of the mass of silicon powder is dispersed, stirring evenly and then drying to obtain an intermediate product;
[0040] (3) The intermediate product is placed in a nitrogen atmosphere, calcined at 500°C for 6 hours, and then transferred to a fluidized bed for gas phase cracking and deposition at 1300°C for 10 hours, with acetylene as the carbon source, to obtain a primary coating product;
[0041] (4) The primary coated product is mixed with liquid asphalt accounting for 15% of the mass of silicon powder, and the solid phase surface is melt-coated at 350°C for 6 hours to obtain a secondary coated product, which is then placed in a nitrogen atmosphere and secondary calcined at 1100°C for 10 hours. The product is sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
[0042] Example 2
[0043] A method for preparing a silicon-based negative electrode material with both high specific capacity and high power comprises the following steps in sequence:
[0044] (1) Nitrogen is introduced into the tank containing ethanol to remove water and oxygen in the tank. The dew point is ≤-30°C and the oxygen content is ≤0.5%. The dried silicon powder is added to the ethanol at a solid content of 10% and mixed evenly. The silicon powder is ground into silicon particles D by a sand mill. 50 ≤60nm, then add tannic acid, a grinding aid, accounting for 8% of the mass of the silicon powder, continue grinding for 3 hours, switch the tank discharge mode, and then add a carbon skeleton (activated carbon) accounting for 5% of the mass of the silicon powder, and continue grinding until the solid content of the silicon slurry at the discharge port is reduced to 25% of the original solid content, and filter with an 800-mesh screen to obtain a carbon skeleton adsorbed with silicon particle units;
[0045] (2) using ethanol to wash away the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution in which a high aspect ratio conductive agent (single-walled carbon nanotubes, with an aspect ratio of 3000) accounting for 0.05% of the mass of silicon powder is dispersed, stirring evenly and then drying to obtain an intermediate product;
[0046] (3) The intermediate product is placed in a nitrogen atmosphere, calcined at 500°C for 6 hours, and then transferred to a fluidized bed for gas phase cracking and deposition at 1300°C for 10 hours, with acetylene as the carbon source, to obtain a primary coating product;
[0047] (4) The primary coated product is mixed with liquid asphalt accounting for 15% of the mass of silicon powder, and the solid phase surface is melt-coated at 350°C for 6 hours to obtain a secondary coated product, which is then placed in a nitrogen atmosphere and secondary calcined at 1100°C for 10 hours. The product is sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
[0048] Example 3
[0049] A method for preparing a silicon-based negative electrode material with both high specific capacity and high power comprises the following steps in sequence:
[0050] (1) Nitrogen is introduced into the tank containing ethanol to remove water and oxygen in the tank. The dew point is ≤-30°C and the oxygen content is ≤0.5%. The dried silicon powder is added to the ethanol at a solid content of 10% and mixed evenly. The silicon powder is ground into silicon particles D by a sand mill. 50 ≤60nm, then add tannic acid, a grinding aid, accounting for 8% of the mass of the silicon powder, continue grinding for 3 hours, switch the tank discharge mode, and then add a carbon skeleton (activated carbon) accounting for 5% of the mass of the silicon powder, and continue grinding until the solid content of the silicon slurry at the discharge port is reduced to 25% of the original solid content, and filter with an 800-mesh screen to obtain a carbon skeleton adsorbed with silicon particle units;
[0051] (2) using ethanol to wash away the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution in which a high aspect ratio conductive agent (single-walled carbon nanotubes, with an aspect ratio of 3000) accounting for 0.1% of the mass of silicon powder is dispersed, stirring evenly and then drying to obtain an intermediate product;
[0052] (3) The intermediate product is placed in a nitrogen atmosphere, calcined at 500°C for 6 hours, and then transferred to a fluidized bed for gas phase cracking and deposition at 1300°C for 15 hours, with acetylene as the carbon source, to obtain a primary coating product;
[0053] (4) The primary coated product is mixed with liquid asphalt accounting for 15% of the mass of silicon powder, and the solid phase surface is melt-coated at 350°C for 6 hours to obtain a secondary coated product, which is then placed in a nitrogen atmosphere and secondary calcined at 1100°C for 10 hours. The product is sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
[0054] Example 4
[0055] A method for preparing a silicon-based negative electrode material with both high specific capacity and high power comprises the following steps in sequence:
[0056] (1) Nitrogen is introduced into the tank containing ethanol to remove water and oxygen in the tank. The dew point is ≤-30°C and the oxygen content is ≤0.5%. The dried silicon powder is added to the ethanol at a solid content of 10% and mixed evenly. The silicon powder is ground into silicon particles D by a sand mill. 50 ≤60nm, then add tannic acid, a grinding aid, accounting for 8% of the mass of the silicon powder, continue grinding for 3 hours, switch the tank discharge mode, and then add a carbon skeleton (activated carbon) accounting for 5% of the mass of the silicon powder, and continue grinding until the solid content of the silicon slurry at the discharge port is reduced to 25% of the original solid content, and filter with an 800-mesh screen to obtain a carbon skeleton adsorbed with silicon particle units;
[0057] (2) using ethanol to wash away the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution in which a high aspect ratio conductive agent (single-walled carbon nanotubes, with an aspect ratio of 3000) accounting for 0.1% of the mass of silicon powder is dispersed, stirring evenly and then drying to obtain an intermediate product;
[0058] (3) The intermediate product is placed in a nitrogen atmosphere, calcined at 500°C for 6 hours, and then transferred to a fluidized bed for gas phase cracking and deposition at 1300°C for 10 hours, with acetylene as the carbon source, to obtain a primary coating product;
[0059] (4) The primary coated product is mixed with liquid asphalt accounting for 25% of the mass of silicon powder, and the solid phase surface is melt-coated at 350°C for 6 hours to obtain a secondary coated product, which is then placed in a nitrogen atmosphere and secondary calcined at 1100°C for 10 hours. The product is sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
[0060] Comparative Example 1
[0061] The difference between Comparative Example 1 and Example 1 is that the single-walled carbon nanotubes with a large aspect ratio conductive agent are not added in step (2).
[0062] Comparative Example 2
[0063] The difference between Comparative Example 2 and Example 1 is that in step (3), no gas phase cracking and carbon deposition is performed, and the solid phase surface is directly mixed with liquid asphalt after one calcination for solid phase surface melting coating.
[0064] Comparative Example 3
[0065] The difference between Comparative Example 3 and Example 1 is that the solid phase surface melt coating and secondary calcination in step (4) are not performed, and the final product is obtained by sieving and packaging after gas phase cracking and deposition.
[0066] Test example
[0067] The products obtained from Examples 1-4 and Comparative Examples 1-3 were subjected to the following tests:
[0068] 1. Alkali foam resistance test: Weigh 0.25g of silicon-based negative electrode material, mix it with 3mL of 1mol / L NaOH solution, seal it in a syringe, and then place it in an environment of 25±2℃, and record the gas production after 24h, 96h, and 168h respectively; the results are shown in Table 1.
[0069] 2. Obtain the SEM image of the silicon-based negative electrode material with high specific capacity and high power obtained in this embodiment, as shown in Figure 2 shown.
[0070] The electrochemical performance of the silicon-based negative electrode material obtained in Example 1 was tested using a CR2032 button half-cell as a model. The specific operating steps are as follows: a slurry is prepared according to a mass ratio of silicon-based negative electrode material: modified polyacrylic acid: conductive carbon black of 8:1:1, the slurry is coated on the surface of a copper foil to form a pole piece, and then the obtained pole piece is dried in a blast oven at 80°C for 2h; a lithium sheet is used as a counter electrode, a polyethylene porous membrane is used as a diaphragm, and a 1MLiPF6 The battery was assembled with electrolyte, and the battery charge and discharge current density was 100mA / g; the results are as follows Figure 3 shown.
[0071] The activated button cell was discharged at a current density of 100 mA / g, and then charged at current densities of 100 mA / g, 300 mA / g, and 500 mA / g, respectively, and the charging capacity was recorded; the test results are shown in Table 2.
[0072] Table 1 Alkali bubble resistance test results
[0073] serial number 24h gas production Gas production in 96 hours Gas production in 168h Example 1 0ml 1.0ml 6.5ml Example 2 0ml 1.5ml 7.0ml Example 3 0ml 0ml 6.0ml Example 4 0ml 0ml 6.0ml Comparative Example 1 0ml 1.0ml 7.0ml Comparative Example 2 2.0ml 3.5ml 12.5ml Comparative Example 3 3.5ml 5.0ml 15.0ml
[0074] Table 2 Rate performance test results
[0075]
[0076] As can be seen from Table 1, in Comparative Examples 2 and 3, vapor deposition cracking carbon attachment or solid surface melting coating is cancelled. Compared with Examples 1-4 and Comparative Example 1, the materials will have obvious gas production in the alkali bubble resistance test. The gas production in the alkali bubble resistance test can equally explain the side reactions of the material in the full battery. The present invention adopts the following scheme: the first layer of carbon coating adopts the vapor deposition method, which can be uniform and dense, and can make up for the defects of the second layer of solid phase coating, isolating the silicon material from contact with the electrolyte. The second layer of carbon coating adopts solid phase melting coating, and the coating layer is thick, which can not only limit the volume expansion of the internal silicon material, but more importantly, it can isolate the silicon material from direct contact with the electrolyte and produce side reactions. It has low cost and is easy to mass produce. The use of gas phase and solid phase double coating effectively improves the side reactions of the material and improves the cycle performance of the material.
[0077] It can be seen from Table 2 that the rate performance of Comparative Example 1 is significantly worse than that of Example 1. The large aspect ratio conductive agent wound in the middle of the present invention can not only improve the rate performance and maintain contact when the silicon material expands, but also has a certain effect of limiting the volume expansion of the silicon material.
[0078] Depend on Figure 2-3 It can be seen that the preparation method of the present invention can successfully obtain a silicon-based negative electrode material with uniform particle size and above 2000 mAh / g.
[0079] In summary, the comprehensive performance of Examples 1-4, such as capacity, rate, and gas production, is significantly better than that of Comparative Examples 1-3. The large aspect ratio conductive agent wound in the middle of the present invention, as well as the double coating of gas phase and solid phase, makes the silicon-based negative electrode material have both high specific capacity and high power. The introduced large aspect ratio conductive agent effectively improves the rate performance of the material; the combination of gas phase cracking carbon attachment and solid phase melt coating can take advantage of each, reduce the amount of amorphous carbon produced by coating, improve the specific capacity of silicon-based materials, and achieve low-cost, high-performance coating.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A silicon-based negative electrode material with both high specific capacity and high power, characterized in that: The invention comprises, from the outside to the inside, a second carbon layer (1), a first carbon layer (2), a large aspect ratio conductive agent winding layer (3) and an inner core, wherein the inner core is a carbon skeleton (4) adsorbed with silicon particle units (5), and the particle size D of the silicon particle units (4) is 95 ≤20nm, the pore size of the carbon skeleton (4) is 10-25nm, the aspect ratio of the high aspect ratio conductive agent is 20-5000, the thickness of the first carbon layer (2) is 1-10nm, and the thickness of the second carbon layer (1) is 5-500nm.
2. The method for preparing the silicon-based negative electrode material with high specific capacity and high power according to claim 1, characterized in that: The following steps are included in sequence: (1) In a nitrogen atmosphere, add the dried silicon powder to the alcohol reagent and mix evenly, then grind to silicon particles D 50 ≤30-100nm, then add a grinding aid, continue grinding for 1-5h, then add a carbon skeleton, continue grinding until the solid content of the silicon slurry at the outlet is reduced to 20-50% of the original solid content, filter, and obtain a carbon skeleton adsorbed with silicon particle units; (2) using an alcohol reagent to clean the silicon particle units on the surface of the carbon skeleton, and then adding them to an ethanol solution dispersed with a conductive agent with a large aspect ratio, stirring evenly and drying to obtain an intermediate product; (3) The intermediate product is placed in an inert atmosphere for a primary calcination, and then transferred to a fluidized bed for gas phase cracking to deposit carbon, thereby obtaining a primary coating product; (4) The primary coated product is mixed with heavy oil and then subjected to solid phase surface melt coating to obtain a secondary coated product, which is then placed in an inert atmosphere for secondary calcination, sieved and packaged to obtain a silicon-based negative electrode material with both high specific volume and high power.
3. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (1), the grinding aid is at least one of acrylic acid, stearic acid, tannic acid and acrylamide, and the amount of the grinding aid added is 1-20% of the mass of the silicon powder.
4. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (1), the carbon skeleton is at least one of porous carbon, activated carbon and foamed carbon, and the carbon skeleton particle size D 50 The particle size is 4-12 μm, and the added amount is 0.5-20% of the mass of silicon powder.
5. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (2), the high aspect ratio conductive agent is at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes and vapor-grown carbon fibers.
6. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (1) and step (2), the alcohol reagent is at least one of ethanol, ethylene glycol, hexylene glycol, isopropanol, allyl alcohol and NMP.
7. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (3), calcination is performed once at a temperature of 400-800°C for 3-20 hours; and vapor phase cracking and deposition is performed at a temperature of 650-1700°C for 5-20 hours.
8. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (3), when the carbon is deposited by gas phase cracking, the carbon source is at least one of methane, acetylene, ethylene and propylene.
9. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power as claimed in claim 2, characterized in that: In step (4), the heavy oil is at least one of solid asphalt and liquid asphalt; the amount of heavy oil added is 2-40% of the mass of the silicon powder.
10. The method for preparing a silicon-based negative electrode material having both high specific capacity and high power according to claim 2, characterized in that: In step (4), the solid phase surface is melt-coated at a temperature of 250-500°C for 5-12 hours; and secondary calcination is performed at a temperature of 600-1200°C for 3-20 hours.
Citation Information
Patent Citations
Silicon-based negative electrode composite material as well as preparation method and application thereof
CN118970021A